Heavy metal and metalloid concentration dynamics in mine and surface waters in the vicinity of Chiprovtsi and Martinovo mines, Northwestern Bulgaria - Dimitrova, D.; Cholakova, Z.; Velitchkova, N.; Kotsev, Ts.; Mladenova, V.; Kerestedjian, T.; Antonov, D. (Bulletin of the Geological Society of Greece, 2007)
Chiprovtsi silver-lead and Martinovo iron mines represent the biggest mining area in Northwestern Bulgaria, which was operated till 1999. Their long-lived operation leads to proved pollution of the environment in the vicinity of the mines, especially water and soil. Seasonal monitoring of heavy metal (Cu, Zn, Cd and Pb) and metalloid (As and Sb) concentrations in mine, surface (river) and drinking waters was carried out during May and August 2006 to determine the level of contamination of the Chiprovska Ogosta river basin resulting from the long-lived mining activity and whether these abandoned mines continue to be potential source for water pollution. This study proves significant As concentrations in mine (up to 170 μg/l) and surface waters (between 50 and 621 μg/l). The presence of other heavy metals, such as Cu, Cd, Zn and Pb, and metalloid — Sb is also recorded. Among them, Pb was found in considerable concentrations - up to 1456 pg/l during May 2006 sampling exhibiting great concentration variability between dry and wet sampling seasons. Sb is also determined in mine waters (up to 25 pg/l), but not exists in surface and drinking waters. Drinking waters are proved to be free of heavy metals and metalloids.